Intestinal liposarcoma: an unusual cause for peritonitis - Gowthaman, Siddartha; Manickam, Ramanathan (International Surgery Journal, 2020)
Liposarcoma is the commonest type of soft tissue sarcomas which can occur in any part of the body, most commonly involving the limbs and retroperitoneum but it rarely involves small bowel. Only very few cases had been reported of liposarcoma involving small intestine in the past. The clinical presentations of this type of tumour arising from small bowel are nonspecific mostly during the initial stages of the disease and because of this the disease is often diagnosed at advanced stage. We report a very rare case of primary small bowel liposarcoma of ileum which had spontaneously perforated leading to peritonitis in an elderly female who underwent laparotomy, the tumour mass is resected with adequate margins and primary bowel anastomosis was done. The patient was followed up for a year with no complication. Although the liposarcomas occurring in the gastrointestinal tract leading to intestinal perforation is extremely rare. This unique case represents an important learning point for all clinicians and pathologists.